Temperature drives pre‐reproductive selection and shapes the biogeography of a female polymorphism - Svensson, Erik I.; Willink, Beatriz; Duryea, Mary Catherine; Lancaster, Lesley T.; Grether, Greg (Ecology letters, 2020)
Conflicts of interests between males and females over reproduction is a universal feature of sexually reproducing organisms and has driven the evolution of intersexual mimicry, mating behaviours and reproductive polymorphisms. Here, we show how temperature drives pre‐reproductive selection in a female colour polymorphic insect that is subject to strong sexual conflict. These species have three female colour morphs, one of which is a male mimic. This polymorphism is maintained by frequency‐dependent sexual conflict caused by male mating harassment. The frequency of female morphs varies geographically, with higher frequency of the male mimic at higher latitudes. We show that differential temperature sensitivity of the female morphs and faster sexual maturation of the male mimic increases the frequency of this morph in the north. These results suggest that sexual conflict during the adult stage is shaped by abiotic factors and frequency‐independent pre‐reproductive selection that operate earlier during ontogeny of these female morphs.